2011
DOI: 10.5539/jas.v4n3p71
|View full text |Cite
|
Sign up to set email alerts
|

Operators’ Capability and Facilities Availability for Repair and Maintenance of Small Tractors in Riau Province, Indonesia: A Case Study

Abstract: This paper presents the capability of tractor operators in performing repair and maintenance of small tractors, the availability of service and repair facilities at the farm level, and the manner of the operators in maintaining their tractors. Data are based on field visits and interviews with 65 tractor operators from 6 villages collected in three regencies of Riau Province. The results show that most operators lack the technical skill to service and repair tractors due to insufficient training, specific educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Participation in training and programs to increase knowledge and technical skills affects the ability of operators to carry out their duties and functions (Paman et al, 2011). Therefore, local governments, especially the Village and Community Empowerment Service (DPMD) often conduct training to improve the competence of village officials and village operators.…”
Section: Village Operator Training Intensitymentioning
confidence: 99%
“…Participation in training and programs to increase knowledge and technical skills affects the ability of operators to carry out their duties and functions (Paman et al, 2011). Therefore, local governments, especially the Village and Community Empowerment Service (DPMD) often conduct training to improve the competence of village officials and village operators.…”
Section: Village Operator Training Intensitymentioning
confidence: 99%
“…This may be due to sufficient knowledge and technical skills in using and maintaining the tractor. A study of operator ability was reported, especially for small tractors [16]. The complexity of farm machinery on the farm today requires more and more versatile know-how to operate and maintain different types and models of farm machines.…”
Section: Introductionmentioning
confidence: 99%
“…Данная машина обладает высокой эффективностью работы, но при этом имеет типичные для данного типа машин недостатки [7]: наличие жестких кинематических связей в приводе РС, большое число передаточных механизмов и изнашивающихся поверхностей, низкая ориентирующая способность зернового материала на решетных станах ЗМ с прямолинейными колебаниями, а также высокие динамические нагрузки.…”
Section: Introductionunclassified
“…1-й этап. Выдвижение гипотезы о законе распределения времени безотказной работы исследуемого объекта [7].…”
Section: Introductionunclassified